Assessing Vegetation Quality for Soil Protection: A Case Study of the Oum Er-Rbia Watershed, Ouled Sidi Driss Upper - Souad Ourabit; Abderrahim Ettaqy; Mohamed El Ghachi (African Journal of Advanced Pure and Applied Sciences, 2023)
Mountainous areas are often colonized by vegetation, which plays a crucial role in protecting soils from degradation. However, this protection varies spatially from one area to another depending on the quality of the vegetation cover. The Oum Er-Rbia watershed (upstream of Ouled Sidi Driss) is a basin inhabited by a variety of vegetation, ranging from natural to artificial. Due to the effects of climate change and human activities, this area experiences soil degradation that varies in space depending on the type of vegetation present and its quality as a means of protection against degradation. In this context, our objective is to study the quality of vegetation as a means of soil protection. To do this, we calculated four sub-indices using a Geographic Information System (GIS): the fire risk index (FR), the drought resistance index (DR), the erosion protection index (EP), and the vegetation cover density index (VC). By overlaying these four sub-indices using the Map Algebra function, we obtained the vegetation quality index (VQI). Our results show that 81% of the watershed’s total area is covered by very low-quality vegetation.